INTERNATIONAL CONFERENCE “STATE, BUSINESS AND CIVIL SOCIETY IN A MODERNIZING RUSSIA: INSTITUTIONS, POLICIES, AND PRACTICES OF POLITICAL INTERACTION” (22–23 NOVEMBER 2013) - статья Редакционная (Сравнительная политика, 2015)
.